2014
DOI: 10.1200/jco.2014.55.6258
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Stage at Diagnosis, Treatment, and Survival in Nonelderly Adult Patients With Cancer According to Insurance Status

Abstract: Purpose The purpose of this study was to determine the association of insurance status with disease stage at presentation, treatment, and survival among the top 10 most deadly cancers using the SEER database. Patients and Methods A total of 473,722 patients age 18 to 64 years who were diagnosed with one of the 10 most deadly cancers in the SEER database from 2007 to 2010 were analyzed. A Cox proportional hazards model was used for multivariable analyses to assess the effect of patient and tumor characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
260
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(279 citation statements)
references
References 27 publications
16
260
2
1
Order By: Relevance
“…The state is composed of urban, rural and suburban populations with percentages similar to that of the United States as a whole; and contains large minority and immigrant populations in the city of Baltimore and the suburbs of Washington, DC. In the United States, the uninsured and those with Medicaid insurance coverage are more likely to present with advanced disease, less likely to receive cancerdirected surgery and/or radiation therapy, and have poorer overall survival than patients with commercial insurance [21]. Travel introduces an additional burden to care affecting both employment and family income, especially if a caregiver accompanies a patient to appointments.…”
Section: Resultsmentioning
confidence: 98%
“…The state is composed of urban, rural and suburban populations with percentages similar to that of the United States as a whole; and contains large minority and immigrant populations in the city of Baltimore and the suburbs of Washington, DC. In the United States, the uninsured and those with Medicaid insurance coverage are more likely to present with advanced disease, less likely to receive cancerdirected surgery and/or radiation therapy, and have poorer overall survival than patients with commercial insurance [21]. Travel introduces an additional burden to care affecting both employment and family income, especially if a caregiver accompanies a patient to appointments.…”
Section: Resultsmentioning
confidence: 98%
“…Prior research has found that Medicaid coverage at the time of cancer diagnosis confers survival benefits. 5 The implication of this work is that access to care before diagnosis is the driver of these benefits. The current results support this assumption by demonstrating that enrollment in Medicaid before diagnosis is associated with early-stage cancer diagnosis.…”
Section: Medicaid Enrollment Timing and Mortalitymentioning
confidence: 99%
“…2 The expansion of Medicaid has been shown to increase use of preventive services, improve access to primary care, and decrease mortality among new enrollees. 3,4 Research has found that having health insurance after a cancer diagnosis improves outcomes, 5 but currently unknown is whether prediagnosis coverage yields additional benefits. Gynecologic cancers encompass screen-detectable (cervical), early-detectable (uterine, vulvar/vaginal), and poorly detectable (ovarian) disease.…”
Section: Introductionmentioning
confidence: 99%
“…Patients who are uninsured or who have government-based insurance including Medicare or Medicaid often present with socioeconomic challenges that inevitably guide their treatment; for example, patients who lack insurance present with more advanced disease, which can contribute to more morbid operations. 9,10 Other factors include transportation issues, willingness for providers to accept them in their practice due to lack of financial incentives, social and financial barriers, and lack of domestic support, which is critical in the postoperative recovery setting. 9,11 Year of diagnosis Perhaps most surprising were the rising rates of upfront hysterectomy followed by RT compared with CRT alone, increasing from 12% to 31% over the past decade.…”
Section: Discussionmentioning
confidence: 99%